Pengujian Undang-Undang Ratifikasi Perjanjian Asean Charter Oleh Mahkamah Konstitusi - Afidatussolihat . (Jurnal Cita Hukum, 2014)
Abstract: Judicial Law Ratification of the ASEAN Charter Treaty by the Constitutional Court. Discourse judicial ratification of international agreements arising from the struggle of ideas that occurred among the stakeholders. There is a positive side and a negative side so that the discourse surface. Constitutional Court's authority extended to test the laws of ratification as a result of the turbulence struggle thinking. Tug of war between national and international interests to be one reason for expantion the authority of the Constitutional Court which is still being debated to this day. Abstrak: Pengujian Undang-Undang Ratifikasi Perjanjian ASEAN Charter Oleh Mahkamah Konstitusi. Wacana pengujian ratifikasi perjanjian internasional muncul akibat pergulatan pemikiran yang terjadi di kalangan para stakeholders. Ada sisi positif dan sisi negatif sehingga wacana tersebut muncul ke permukaan. Kewenangan Mahkamah Konstitusi diperluas untuk menguji undang-undang ratifikasi sebagai hasil dari turbulensi pergulatan pemikiran tersebut. Tarik menarik antara kepentingan nasional dengan internasional menjadi salah satu alasan perluasan kewenangan Mahkamah Konstitusi yang masih menjadi perdebatan hingga saat ini. DOI: 10.15408/jch.v1i1.1459